KRISTAL HEMOGLOBIN PADA BERCAK DARAH YANG TERPAPAR OLEH BEBERAPA DETERJEN BUBUK MENGGUNAKAN TES TEICHMANN DAN TES TAKAYAMA - Serli Marcelisa; Enikarmila Asni; M. Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBloodstain is one of the body fluid which might drop in some criminal case. Investigating bloodstain is very useful to solve a criminal case and can be an evidance. There are some ways to eliminate the evidance for example wash the bloodstain from victim’s cloth. The purpose of this research are to know the description of hemoglobin crystal exposed by some detergent powder using Teichmann test and Takayama test. Teichmann test and Takayama test are forensic laboratory examination that can help to prove the formation of hemoglobin crystals. The reserch was an experimental study conducted in a University Medical School Biochemistry Laboratory Riau. Exposure method in this research is to be streamed. The results of this research was still finding hemoglobin crystals in 14 (100%) slide that have been drained of bloodstain using 7 brand deterjen powder. The conclusion of this reserch is bloodstain that has beeb exposed to detergent powder still gaves an overview of hemoglobin crystals.Keywords : bloodstain, detergent powder,hemoglobin crystals, Teichmann test, Takayama test